Reviewing the importance of diversity in high performance teams / Azlyn Ahmad Zawawi and Aizzat Mohd. Nasurdin - Zawawi, Azlyn Ahmad; Mohd. Nasurdin, Aizzat (Universiti Teknologi MARA, Kedah, 2018)
High performance teams are essential to organizational functioning and even more when the members are diverse in terms of background, knowledge and skills. Team diversity impacts team performance as it inculcates variation of ideas, induces creativity, stimulates brainstorming, and reduces stereotypes and group bias. Besides, with team diversity, team members are able to value differences in terms of members’ background, views, and perspectives. Extant review of the literature suggests that diversity is pivotal to performance, thus, this paper aims to review the importance of team diversity on high performance teams. The concept of high performance teams is discussed in this paper, along with scholarly definition of team and team types. It is concluded that team diversity plays a critical role in the success of high performance teams.